Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini) - Zilberman, Bruno (Zootaxa, 2019)
Termitozophilus Silvestri 1901 is a Neotropical genus of termitophilous beetles, with two species, T. laetus Silvestri, 1901 and T. mirandus (Mann, 1923), in subtribe Timeparthenina Silvestri, 1901, which is a sister group of the remaining Corotocini Fenyes, 1918. A new species, Termitozophilus belleae sp. nov., from Brazil, is described and illustrated. The genus and the other two species are redescribed and illustrated, and morphological and general discussion of host, taxonomic information and key to species are present.